Features of Formation of Regional Reproductive Proportions in Modern Conditions Annotation - E.Rovenskikh, Igor; P. Belikova, Tamara; A.Syrovatskaya, Tatyana; A. Shamrina, Eraterina (International Journal of Engineering and Technology, 2018)
The article considers the approaches to regional development and management of regional subsystem. The processes of management of territorial organization of production are researched from the standpoint of reproduction approach. The approaches to strategic management of the region in modern conditions are analysed. The main contradictions, which the management system faces in modern conditions, are revealed, and the ways of their overcoming are shown.Â Â Â